Paradiplomacy in Preparation for the Nation's Capital in East Kalimantan - Enny Fathurachmi; Burhanuddin Burhanuddin; Andi Purnawarman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The selection of East Kalimantan to be the candidate for the Capital of the New State of Indonesia, provides an opportunity for the region to be more open to open international cooperation with local governments and cities from other countries. Paradiplomasi becomes a vehicle for local governments to be able to cooperate with foreign parties. This paper intends to expose the reality of foreign cooperation that is still minimally carried out by the East Kalimantan Regional Government.  The idea of this paper departs from the many initiations of cooperation carried out by local governments but many only stop at the levelof Memorandum of Understanding (MOU)withoutfollow-up to the realization of the implementation of cooperation agreements.  Departing from the reality of this paper offers ideas by taking the momentum of the National Capital in East Kalimantan to prepare by collaborating with various parties to encourage the East Kalimantan government to be more active in realizing foreign cooperation to encourage development in East Kalimantan on a global scale.